Disease and death: The shock wave of collective punishment against Gaza - Marcos Arana-Cedeño (Social Medicine Publication Group, 2024)
A few days after the South African government filed an indictment against Israel for genocide at the International Court of Justice in The Hague, and a hundred days into Israel's ongoing military offensive, the civilian death toll has surpassed 26,000 and the number of injured people has exceeded 60,000. Although the casualties continue to rise at an average rate of 125 deaths per day,1 the greatest threat comes not from shelling, but from hunger and disease.